Designing of superporous cross-linked hydrogels containing acrylic-based polymer network - Ray, Debajyoti; Sahoo, Prafulla Kumar; Mohanta, Guru Prasad (Asian Journal of Pharmaceutics (AJP), 2014)
Biodegradable cross-linked polymer, 2-hydroxyethyl methacrylate-co-acrylic acid was synthesized by free radical polymerization technique using N,Nâ€-methylene-bis-acrylamide as cross-linker and benzoyl peroxide as reaction initiator. FT-IR, 1H-NMR, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA) studies of the copolymer along with homopolymers were carried out. FT-IR studies showed no interactions on copolymerization. SEM studies of the copolymer were carried out and mean particle size was found to be 50 Î¼m. TGA analysis indicated an increase in thermal stability by cross-linking the polymer network. Swelling behavior of the copolymer showed more swelling by increasing pH of the medum and the prepared polymer was found to be biodegradable. The prepared cross-linked polymer system holds good for further drug delivery studies in connection to its super swelling and biodegradability.